Análise da teoria democrática contemporânea: um estudo crítico sobre Joseph Schumpeter - Souza, Ronaldo Tadeu de (2008)
This aims at studying the contemporary democratic theory, specifically, the study of theory elitist democracy of Joseph Schumpeter. The democratic theory and after World War II was decisively influenced by the ideas of democracy of Joseph Schumpeter. This means that the discipline of political science was also influenced by the ideas of democracy elitist of Schumpeter. The theory of Schumpeter on democracy sought resolve the question of how to limit the participation and assistance from the man of the people in the decisions of state. To answer this Schumpeter draws on some variables. Among those highlighted the parameters of the English parliamentary system and functionality of the social democrat parties. These two variables allowed Joseph Schumpeter to define democracy as an institutional method that allows the selection of leaders through the fight for votes of the people. Several authors and democratic currents had criticized the theory of limited democracy in the Austro-American economist, for example: the participativistas Carole Pateman and Peter Bachrach and deliberativista Jürgen Habermas, but all were inadequate. So I chose undertake this critical study from the Marxist political theory, more precisely the Marxist theory that was contemporary with Joseph Schumpeter, namely the Marxist theory of the beginning of this century. This is also justified by the fact that Schumpeter himself in his work "Capitalism, Socialism and Democracy" undertakes a critique of Marxist socialism to build his theory of democracy based on leadership and the exclusion of people from politics. Our method was to analyse the main points of the central text of "Capitalism, Socialism and Democracy", namely the text of Part IV - "Socialism and Democracy." We also use as a method historical research-politician who served on Schumpeter to build their own theory. Our hypothesis is that the theory of democratic leadership of Joseph Schumpeter was an attempt to develop a conceptual structure that would allow the continuation of the unstable equilibrium of the bourgeois domination